Assessment of the potential respiratory hazard of volcanic ash from future Icelandic eruptions: A study of archived basaltic to rhyolitic ash samples - Damby D. E.; Horwell C. J.; Larsen G.; Thordarson T.; Tomatis M.; Fubini B.; Donaldson K. (Environmental Health, 2017)
Background: The eruptions of Eyjafjallajökull (2010) and Grímsvötn (2011), Iceland, triggered immediate, international consideration of the respiratory health hazard of inhaling volcanic ash, and prompted the need to estimate the potential hazard posed by future eruptions of Iceland's volcanoes to Icelandic and Northern European populations. Methods: A physicochemical characterization and toxicological assessment was conducted on a suite of archived ash samples spanning the spectrum of past eruptions (basaltic to rhyolitic magmatic composition) of Icelandic volcanoes following a protocol specifically designed by the International Volcanic Health Hazard Network. Results: Icelandic ash can be of a respirable size (up to 11.3 vol.% < 4 μm), but the samples did not display physicochemical characteristics of pathogenic particulate in terms of composition or morphology. Ash particles were generally angular, being composed of fragmented glass and crystals. Few fiber-like particles were observed, but those present comprised glass or sodium oxides, and are not related to pathogenic natural fibers, like asbestos or fibrous zeolites, thereby limiting concern of associated respiratory diseases. None of the samples contained cristobalite or tridymite, and only one sample contained quartz, minerals of interest due to the potential to cause silicosis. Sample surface areas are low, ranging from 0.4 to 1.6 m2 g-1, which aligns with analyses on ash from other eruptions worldwide. All samples generated a low level of hydroxyl radicals (HO•), a measure of surface reactivity, through the iron-catalyzed Fenton reaction compared to concurrently analyzed comparative samples. However, radical generation increased after 'refreshing' sample surfaces, indicating that newly erupted samples may display higher reactivity. A composition-dependent range of available surface iron was measured after a 7-day incubation, from 22.5 to 315.7 μmol m-2, with mafic samples releasing more iron than silicic samples. All samples were non-reactive in a ...